Technology for monitoring tremor in the upper extremities of patients with Parkinson's disease: a systematic review and a proposal (LACCEI, 2024)
PD patients come to experience a wide spectrum of cognitive, psychiatric, non-motor and motor symptoms. Tremor is one of the initial symptoms described by 70% of patients diagnosed with PD and quantifying it will allow the specialist to know the evolution of his patient and the possible treatment to implement. The objective of this research is to identify systems, devices or instruments and the methods used to monitor tremors that affect the upper extremities of patients with PD. In addition, this work proposes an initial prototype system that allows the capture of involuntary movements that occur in patients with PD. It was observed that the largest number of articles use their monitoring devices in controlled environments and despite the fact that there are many studies that are developing devices for monitoring tremors in the upper extremities, more efforts are still needed in this area. Many studies conclude that using IMU sensors has proven to be a good technique that allows monitoring of tremors. Other results obtained show that the proposed prototype works correctly, since when compared with a commercial application on a cell phone, very similar values are obtained, demonstrating its proper functioning.